BASIC CONCEPTS OF EDUCATIONAL SUPERVISION ALONG WITH RELATED ADMINISTRATIVE STUDIES - Yudhie Suchyadi; Sri Rini Indriyani; Dita Destiana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Sematically educational supervision is coaching in the form of guidance or guidance towards improving the educational situation in general and improving the quality of teaching and learning and learning in particular. In general, educational administration contains various purposes that are tailored to the field and science of administration, one of which is educational administration. Every administration implementation is always directed towards the goals and objectives to be achieved. When coupled with the context of the purpose of educational administration, the role of administration is used as a supporter of the success of the implementation of education to achieve educational goals. Educational Administration deals with all materials, teacher personnel, planning, cooperation, leadership, curriculum, and student affairs and others. Everything can be managed properly if there is good educational administration, firm leadership, and it is impossible to achieve unwanted goals. If there is no good educational administration, it is impossible for everything to go well. Administration is also the main source of management in managing the teaching and learning process in an orderly manner so that the achievement of the most important goals in educational institutions and Educational Administration does not only discuss notes, finances, but how we can carry out the organizational process according to what we have planned. effectively and efficiently. Education Administration Services in schools, it can be said that they are well supported by the existence of services (1) Curriculum administration services, (2) Public Relations administration services, students at the acceptance of new students, (3) Facilities and infrastructure administration services, (4) ) Financial management, (5) Student administration services  through online which can be accessed through the Basic Education Data application. (3) Managerial Supervision in Improving Educational Administration Services in schools, with managerial supervision carried out by supervisors who have work programs in each section of educational administration services can improve the performance of educational administration services. By assessing, monitoring and fostering educational administration services in schools.